Feeding lines: Standing up in the neoliberal charitable food regime. Issue 2 (July 2023) - Lohnes, Joshua; Pine, Adam
This review explores the production and management of hunger under capitalism through the work of four scholars' embeddedness with expanding feeding lines in rich but unequal countries of the Global North. We engage with their methodologies, placing the material and discursive infrastructures undergirding the explosion of charitable food networks within the rich literature on food and hunger in geography. Bringing Food Bank Nations, Feeding the Crisis, Feeding the Other, and A Mass Conspiracy to Feed People in conversation reveals the critical function that charitable food assistance plays in revaluing food waste on behalf of the corporate food regime and disciplining people navigating precarious life in urban spaces. We also highlight the possibilities that the fraught politics of the feeding line afford to scholar activists and activist scholars advancing movements for food justice, food sovereignty, and the right to food.